Photosynthetic activity, photoprotection and photoinhibition in intertidal microphytobenthos as studied in situ using variable chlorophyll fluorescence - Serôdio, João
The photosynthetic activity of microphytobenthos biofilms was studied in situ on an intertidal mudflat of the Ria de Aveiro, Portugal. Time series of physical variables characterizing the microenvironment at the sediment photic zone (incident solar irradiance, temperature, salinity), photophysiological parameters and productive biomass of undisturbed microalgal assemblages were measured during daytime low-tide periods along one spring–neap tidal cycle, with the objective of (1) characterizing the short-term variability in photosynthetic activity in situ, (2) relating it with the changing environmental conditions and (3) with the operation of physiologically (xanthophyll cycle) and behaviorally (vertical migration) based photoprotective processes, and (4) assessing the occurrence of photoinhibition. Pulse Amplitude Modulated (PAM) fluorometry was applied to measure photosynthetic activity (the effective and maximum quantum yield of photosystem II, ΔF/Fm′ and Fv/Fm; the photosynthesis index EFY; rapid light-response curves (RLC)), the photoprotective operation of the xanthophyll cycle and photoinhibition (non-photochemical quenching, NPQ; quantum efficiency of open RCs, Fv′/Fm′), and vertical migration (productive biomass, Fo). The photosynthetic activity was found to be strongly affected by the cumulative light dose received during the morning low-tide periods. The fluorescence indices ΔF/Fm′, EFY, Fv′/Fm′ and RLC parameters were more depressed under high irradiances when clear sky was present during the morning low tide than when foggy conditions reduced the light dose received during a comparable period. Productive biomass exhibited maximum values in the first hours of the morning, followed by a steep decrease when irradiance reached moderate levels, due to the downward migration of the microalgae. This photophobic migratory response appeared to display a photoprotective role, allowing ΔF/Fm′ to remain near optimum values until irradiance reached values as high as 750 μmol m−2 s−1. The response to high light also included the formation of NPQ, expected to represent mainly the operation of the xanthophyll cycle, which attained high values, above 5.9 for 1500 μmol m−2 s−1. Despite the photoprotection provided by energy-dissipation processes and photophobic behaviour, the light response of most photophysiological parameters showed a clear counter-clockwise hysteresis pattern, indicating the occurrence of photoinhibition. Hysteresis was due to the incomplete recovery of photosynthetic activity during the afternoon low tide, and its magnitude was dependent on the morning light doses.